Sleep, Worker's Health, and Social Welfare - Yoshida, Ken (Business Management and Strategy, 2022)
The aims of this paper are to construct a theoretical model treating sleep as an investment in health capital and analyze how sleep affects a worker's health capital and social welfare. We consider time constraints because sleep only requires time, and we assumed that consumption also requires time. By doing so, we reveal how workers decide their hours slept. Of particular importance is the result that workers store their health capital by sleeping more than the optimal value at a young age, which leads to increased output. Moreover, we identify a complementary relationship between consumption and labor supply. These results show that policies to reduce hours worked could improve workers' health capital and social welfare.